Hard Coal Subsidies: A Never-Ending Story? - Manuel Frondel; Rainer Kambeck; Christoph M. Schmidt (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2006)
In Germany, hard coal has been subsidized for almost half a century. Despite the declining significance of hard coal production for the domestic labor market, the magnitude of subsidies increased until the middle of the last decade. In 1996, they peaked at 6.7 bill.While German hard coal subsidies have been shrinking to 2.7 bill. in 2005, it is very likely that they will be extended well into the next decade and even beyond. This article discusses the feeble arguments raised by the proponents of hard coal subsidization in Germany and other EU countries. Most importantly, in addition to the drain imposed on public budgets, these subsidies imply a substantial opportunity cost, leading funds away from alternative, more beneficial public investments. From a social welfare perspective, we therefore recommend the rapid abolition of these subsidies not only in Germany, where in nominal terms the accumulated amount of subsidies has now by far exceeded 130 bill., but all across Europe.
Keywords: Q42; Q28; Q58; 330; Energy policy; energy security; coal mining